A study of optimization methods for 3D reconstruction from 2D sketches - Kotlanka Ramakrishna. (2008)
This dissertation studies a specific process “Optimization of geometric reconstruction” in the problem of converting a 2D line drawing in to a 3D model. The solution being offered consists of two parts: identifying the circuits of edges in the drawing that form true faces of the 3D models, and then reconstruct the geometry using these faces as a basic.